Transitioning into the Rural Clean Energy Issues in Developing Country: South Asian Perspectives - Chapagai, Durga Prasad; Dhusiya Sharma, Neeta Dhusiya Sharma; Roy, Manish Kumar Roy; Roy, Amit Kumar (Journal of Business and Management, 2024)
Background: Energy transitions are a key topic in emerging economies, driven by fuel price fluctuations, environmental concerns, technological advancements, and energy accessibility goals. South Asia faces challenges in achieving clean, sustainable energy access, with energy poverty in rural areas despite economic growth.Objectives: This study investigates the challenges encountered in rural energy transitions across South Asia, intending to foster connections and academic understanding. It also critically examines current events and trends in energy transformation within the region.Methods: This study uses a systematic literature review (SLR) to identify trends and gaps in the transition to clean energy, employing clear objectives, inclusion criteria, comprehensive searches, relevance screening, data extraction, and critical appraisal.Results: The Maldives leads with 99.5 percent clean energy access, followed by Bhutan at 79.5, India at 56.9, and Bangladesh at 9.5 percent. Key issues include underdeveloped Information communication and technology (ICT), limited regional cooperation, inadequate capital investment, energy equity disparities, socioeconomic factors, political and legal issues, and tariff and subsidy concerns.Conclusion: The region faces various socioeconomic barriers to rural clean energy access. It advocates for implementing evidence-based interventions to facilitate the transition to renewable energy and effectively mitigate the challenges identified in the analysis.JEL Classification: Q2, Q3, Q4, Q5